Inverstigation of corneal and lens densitometry in eyes of patients with primary myelofibrosis (Annals of Medical Research, 2021)
Aim: To investigate the corneal-lens densitometry and endothelial cells of Primary myelofibrosis patients.Materials and Methods: We evaluated 49 eyes of 49 primary myelofibrosis patients on follow up in hematology clinic and compared to 46 eyes of 46 age and sex-matched control group . The Scheimpflug images of 90–270 degrees by Pentacam HR (Oculus Optikgeräte GmbH, Wetzlar, Germany) were used for measurement. After pupil dilatation, the corneal apex was marked by pentacam automatically and the diameter of central 6 mm around marked point was analyzed. PNS (Pentacam Nuclear Staging) software was used for densitometric analysis of the lens from a cylindrical region in the nucleus center. Specular Microscope CEM-530 (Nidek, Japan) was used for endothelial cell analysis. Results: There was no statistically significant difference between groups for age and gender(Table1). Corneal density and corneal volume were higher in the patient group but it was not statistically significant (respectively p=0.390, p=0.078). Lens density was found as statistically significantly higher in the patient group compared to the control group(p0.001). For the corneal endothelial analysis by specular microscopy, there was no statistically significant difference for cell density, the coefficient of variant and endothelial hexagonality (respectively, p=0.546, 0.671, 0.103).Conclusion: Primary myelofibrosis does not affect corneal densitometry and corneal endothelial cells. However, there is a higher lens densitometric measurement in Primary myelofibrosis compared to the control healthy group.
Keywords: Corneal densitometry; lens densitometry; primary myelofibrosis; specular microscopy